Reflections on India’s ‘Guidelines on Cross Border Trade of Electricity’ Vis-a-vis Nepal’s ‘Electricity Development Decade 2016/’026’ and ‘2017/’018 Budget’ - Pun, Santa Bahadur (Hydro Nepal: Journal of Water, Energy and Environment, 2017)
Nepal unfurled her 10,000 MW in 10 years Electricity Development Decade 2016/’026 in February 2016 supposedly with one eye on her own domestic consumption but definitely with the other eye on India’s growing hungry market. India, for ‘strategic, national and economic’ reasons, issued her Guidelines on December 5, 2016 whereby preferential treatment is given to Indian entities that wish to export power from Nepal to India. While Indian entities with 51% or more ownership require a one-time approval, all other participating entities are eligible to participate on ‘case to case basis.’ The concerned authorities of Nepal, thick-skinned as they are, made no fuss at all about India’s Guidelines. In fact, Nepal held the 5th Power Summit on December 16, 2016 concluding that, though the 10,000 MW is ambitious, it is realistic and achievable. In the immediate aftermath in January 2017, the USAID financed Delhi-based IRADe launched its report in Kathmandu wherein the Nepalese media was all agog reporting ‘Nepal can earn Rs 1 Trillion a year by selling power.’ This was then followed by the Nepal Investment Summit jamboree in March 2017 that boasted of garnering 13.6 billion US$ foreign commitments. All these were then topped by the Nepal government’s 2017/’018 budget that sanguinely hiked up the “10,000 MW in 10 years’ to an inconceivable ‘17,000 MW in 7 years!’Sans the electricity regulatory commission, sans the Indo-Nepal downstream benefit sharing mechanism from storage projects and sans the huge required capital skillfully throttled by India’s Guidelines, Nepal’s 17,000 MW in 7 years is an extremely tall order, more likely to end up in the manner of Som Sharma’s sattu! HYDRO Nepal JournalJournal of Water Energy and EnvironmentIssue: 21, July, 2017Page: 5-10Upload Date: July 18, 2017